Maintaining government dominance albeit the pandemic, the governance of sport legacy of the 2022 Beijing Olympic winter games in the time of COVID-19 - Hu, X.; Bairner, A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Introduction The study aims to scrutinises the way in which the governance of the sport legacy of the Beijing Winter Olympics has been changed in the pandemic circumstance. In particular, given the dominance of government in the Chinese society and the significance of cross-sector coalition in governance network, it is sought to not only examine the changes and continuities in the power relations between stakeholders but also reveal how the government has skilfully maintained its dominance in Olympic sport legacy governance in the time of COVID-19. Methods A multi-dimensional governance approach, which is recognised as one covering all the different facets that are associated with the notion of `governance` (Lange et al. 2013, p. 409), is employed in the study in order to examine the institutional, procedural and political aspects of governance (Byun and Leopkey 2020) through analysing qualitative data collected through two rounds of interviews with 26 personnel holding managerial position in Chinese governments, BOCOG 2022, and private organisations related to the Beijing Olympic Winter Games. Results The study scrutinises various impact of the COVID-19 on legacy governance through revealing changes in the policy, polity and politics dimension of the governance of two sport legacy goals specified by BOCOG 2022. We also interrogate the relationship between, and the essence of, the changes and continuities in different dimensions of legacy governance. Discussion Even though the concept of governance emphasises self-coordinating, inter-organisational coalition or ruling through and by networks, the Chinese government has craftily maintained its dominance in an intangible fashion through a medium, i.e., knowledge, which both influences and is influenced by discourse, which "legitimates social actions and relations between those who shape the normative conventions and whose life experiences may be shaped by such conventions" (Chatziefstathiou and Henry 2012, p.13). It is thus contended that governance, despite the non-hierarchical characteristics of the concept, is societally restrained by the hierarchical structure of the society in which it operates and functions with a power hierarchy that is controlled by the government even in a less tangible and/or more subtle manner.